IRF6 and SPRY4 Signaling Interact in Periderm Development. (October 2017) - Kousa, Y.A.; Roushangar, R.; Patel, N.; Walter, A.; Marangoni, P.; Krumlauf, R.; Klein, O.D.; Schutte, B.C.
Rare mutations in IRF6 and GRHL3 cause Van der Woude syndrome, an autosomal dominant orofacial clefting disorder. Common variants in IRF6 and GRHL3 also contribute risk for isolated orofacial clefting. Similarly, variants within genes that encode receptor tyrosine kinase (RTK) signaling components, including members of the FGF pathway, EPHA3 and SPRY2, also contribute risk for isolated orofacial clefting. In the mouse, loss of Irf6 or perturbation of Fgf signaling leads to abnormal oral epithelial adhesions and cleft palate. Oral adhesions can result from a disruption of periderm formation. Here, we find that IRF6 and SPRY4 signaling interact in periderm function. We crossed Irf6 heterozygous ( Irf6 +/– ) mice with transgenic mice that express Spry4 in the basal epithelial layer ( Tg KRT14::Spry4 ). While embryos with either of these mutations can have abnormal oral adhesions, using a new quantitative assay, we observed a nonadditive effect of abnormal oral epithelial adhesions in the most severely affected double mutant embryos ( Irf6 +/– ;Tg KRT14::Spry4 ) . At the molecular level, the sites of abnormal oral adhesions maintained periderm-like cells that express keratin 6, but we observed abnormal expression of GRHL3. Together, these data suggest that Irf6 and RTK signaling interact in regulating periderm differentiation and function, as well as provide a rationale to screen for epistatic interactions between variants in IRF6 and RTK signaling pathway genes in human orofacial clefting populations.